Teaching Arabic in kindergarten – A field study of Najmeyn Kindergarten in the municipality of M’sila. - boussakra, amar; abdeslam, salima (El Omda in Linguistics and Discourse Analysis, 2025)
This study dealt with the subject of teaching Arabic in kindergarten, i.e. children in the pre-school stage or what is known as early childhood, where the child is more capable of learning and acquiring linguistic and cognitive experiences. It is a field study conducted in the Wilayat of M'sila in Al-Kia neighborhood in the municipality of Messila, using the descriptive approach and its most important research tools, represented in the interview, observation, documents and records, and this is due to the nature and requirements of the study, where we reached a conclusion that: The teaching aids adopted in the kindergarten enable those in charge of the process to achieve the objectives due to their cognitive and formative experience, which facilitated this in enabling children at this stage to the basics of reading, writing, memorization and retrieving acquired knowledge.